2021
DOI: 10.1002/adfm.202105184
|View full text |Cite
|
Sign up to set email alerts
|

Band‐Like Charge Transport in Phytic Acid‐Doped Polyaniline Thin Films

Abstract: We explore the charge transport properties of phytic acid (PA) doped polyaniline thin films prepared by the surfactant monolayer‐assisted interfacial synthesis (SMAIS). Structural and elemental analysis confirms the inclusion of PA in the thin films and reveals a progressive loss of crystallinity with the increase of PA doping content. Charge transport properties are interrogated by time‐resolved terahertz (THz) spectroscopy. Notably, independently of doping content and hence crystallinity, the frequency‐resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Impurity scattering likely weakens the temperature dependence of the mobility. 36 , 50 , 51 The presence of defects is further evidenced by a correlation between the charge scattering time and charge carrier lifetime in our samples: compared to sample A used for the OPTP studies (shown in Figure 2 ), we noticed a reduced charge scattering time at room temperature (from 72 to 41 fs) in sample B used for the temperature-dependent measurements. This is accompanied by a reduction in the charge carrier lifetime ( Figure S6 ).…”
Section: Resultssupporting
confidence: 55%
“…Impurity scattering likely weakens the temperature dependence of the mobility. 36 , 50 , 51 The presence of defects is further evidenced by a correlation between the charge scattering time and charge carrier lifetime in our samples: compared to sample A used for the OPTP studies (shown in Figure 2 ), we noticed a reduced charge scattering time at room temperature (from 72 to 41 fs) in sample B used for the temperature-dependent measurements. This is accompanied by a reduction in the charge carrier lifetime ( Figure S6 ).…”
Section: Resultssupporting
confidence: 55%
“…During the polymerization process, the primary amine group of aniline is oxidized to form nitrenium, which subsequently reacts with the para-hydrogen atom of another aniline molecule through the electrophilic substitution. [70][71][72] Due to the unique role of GO, PANI arrays vertically grow on the GO surface to produce p-electron-enriched PG (Figure 2b). The PANI nanocone arrays on GO effectively block the exposure of oxygen-containing moieties of GO and suppress restacking of GO.…”
Section: Surface Topography Modulationmentioning
confidence: 99%
“…Using this synthetic strategy, they first achieved the wafer scale quasi-2D (q2D) polyaniline (PANI) thin film synthesis underneath the water surface. 122,123 In the synthesis procedure, the surfactant monolayer was first prepared by spreading the surfactant/chloroform solution on the water surface, and then the monomer aniline was injected into the water subphase to diffuse and adsorb underneath the surfactant monolayer (Fig. 10(a)).…”
Section: Surfactant-monolayer Assisted Interfacial Synthesismentioning
confidence: 99%